2014
DOI: 10.1016/j.devcel.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

IFT27 Links the BBSome to IFT for Maintenance of the Ciliary Signaling Compartment

Abstract: Vertebrate hedgehog signaling is coordinated by the differential localization of the receptors patched-1 and smoothened in the primary cilium. Cilia assembly is mediated by intraflagellar transport (IFT) and cilia defects disrupt hedgehog signaling, causing many structural birth defects. We generated Ift25 and Ift27 knockout mice and show they have structural birth defects indicative of hedgehog signaling dysfunction. Surprisingly ciliary assembly is not affected, but abnormal hedgehog signaling is observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
354
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(378 citation statements)
references
References 36 publications
19
354
5
Order By: Relevance
“…IFT27 was recently shown to play a crucial role in facilitating ciliary exit of the BBSome (Eguether et al, 2014;Ng et al, 2012), and Ift27-deficient mouse embryonic fibroblasts are unable to maintain low levels of SMO in the cilia when the Hh pathway is inactive (Eguether et al, 2014). In this study, we further demonstrated that suppressed Hh signaling in Ift27 −/− primary dermal fibroblasts is also associated with abnormal accumulation of SMO in the cilium.…”
Section: Ift27supporting
confidence: 59%
See 2 more Smart Citations
“…IFT27 was recently shown to play a crucial role in facilitating ciliary exit of the BBSome (Eguether et al, 2014;Ng et al, 2012), and Ift27-deficient mouse embryonic fibroblasts are unable to maintain low levels of SMO in the cilia when the Hh pathway is inactive (Eguether et al, 2014). In this study, we further demonstrated that suppressed Hh signaling in Ift27 −/− primary dermal fibroblasts is also associated with abnormal accumulation of SMO in the cilium.…”
Section: Ift27supporting
confidence: 59%
“…Ift27 −/− and Ift25 −/− mice die shortly after birth due to severe developmental abnormalities in vital organs, such as the heart, spinal cord and lung (Eguether et al, 2014;Keady et al, 2012). These developmental anomalies were linked to disrupted Hh signaling (Eguether et al, 2014;Keady et al, 2012). The extensive phenotypic outcome in Ift27 −/− and Ift25 −/− mice suggests that this subset of IFT proteins might be widely required in the embryonic development of complex organ systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LZTFL1 mutations were then found in human patients with BBS, rendering it the 17th BBS gene (BBS17) (24,25). More recently, it was shown that Lztfl1 cycles between cilia and the cytoplasm and facilitates removal of the BBSome from cilia (26). In this work, we sought to determine the physiological roles of BBS proteins in photoreceptors and mechanisms of photoreceptor degeneration by using a newly developed Lztfl1 mutant mouse line and quantitative analyses of the OS proteome.…”
Section: Significancementioning
confidence: 99%
“…This could be important given that trypanosomes swim with the flagellum forward and use the flagellum to attach to the epithelium of the salivary glands during infection in the tsetse fly (Tetley and Vickerman, 1985). Signalling molecules could also be concentrated depending on IFT (Eguether et al, 2014).…”
Section: Ift and The Maintenance Of Flagellar Componentsmentioning
confidence: 99%